Role of Oxygenation Saturation Index as a Predictor of Clinical Outcome of Acute Respiratory Distress Syndrome Patients in ICU (Bangladesh Critical Care Journal, 2026)
Background: Acute respiratory distress syndrome (ARDS) continues to pose major prognostic challenges, with high mortality rates and traditional oxygenation indices limited by their reliance on invasive arterial blood gas measurements. Growing evidence supporting noninvasive markers such as the ratio of oxygen saturation in pulse oximetry and fraction of inspired oxygen (SpO₂/FiO₂) and oxygen saturation index (OSI) prompted this study to explore OSI as a safer, practical predictor of clinical outcomes in critically ill ARDS patients. Methods: This prospective observational study enrolled 150 adult ARDS patients at Dhaka Medical College Hospital, following strict Berlin diagnostic criteria and PEEP-supported ventilation. After obtaining ethical approval and informed consent, detailed demographic, clinical, and comorbidity data were collected at admission. Daily monitoring during the first four ICU days included hemodynamics, ventilator settings, ABG analysis, and calculation of APACHE II, Oxygenation Index (OI) and Oxygenation Saturation Index (OSI) values. Key outcomes, ventilation duration, length of ICU stay, multiorgan failure, and hospital mortality, were recorded to evaluate the predictive performance of oxygenation indices. Result: Most of the study population were in older age groups, with males comprising 64% and occupations spanning service, business, day labour, and household roles. Hypertension (48%), smoking (40%), diabetes (32%), and obesity (20%) were the major risk factors, while severe traumatic injury (48%) and sepsis-related causes dominated the etiological profile. In-hospital mortality was 36%, and patients experienced prolonged ventilation, ICU stay, and hospitalization. Multiple variables, including age (p